Effects of Cd on hepatic GSH metabolism in T. nilotics - HUI Tian-chao; WANG Jia-gang; ZHU Ying-mei (浙江大学学报. 农业与生命科学版, 2001)
T. nilotics were exposed in 0.3 mg/L Cd and 3.0 mg/L Cd water for 8 days. In those days, Hepatic Cd, GSH, GCS and GST were assayed. The results show that hepatic Cd accumulation is strongly positive correlated with exposure time; Content of GSH was elevated by low concentration of Cd with Cd accumulating in liver. The main mechanism is that low dosage of Cd can stimulate the activities of GCS and GST, but the quantity of synthesis is greater than that of consumption. On the contrary, higher dosage of Cd can decrease GSH synthesis via inhibiting GCS activity and speed the consumption of GSH via stimulating the activity of GST indirectly, so hepatic GSH content is decreased.